Supravengricular tachycardia in children: The role of infectious diseases and its relationship to serum enzyme - A. Samik Wahab, A. Samik Wahab (Universitas Gadjah Mada, 1986)
In twenty four children an episode of supraventricular tachycardia occurred before 15 years (median age 12 months). Fourteen male and 10 female children were reviewed, of which one had a congenital heart disease. Lown-Ganong-Levine syndrome was present on surface ECG in 1/24 (4 per cent). Forty six per cent of children were undernourished as determined by the weight to height ratio according to the WHO criteria (1983), and 58 per cent of them were anemic, according to the WHO criteria (1972). All children have had fever, mostly above 38.5ÃÂ° C. In ten children with an SVT episode the serum enzyme level, was also studied, i. e. the serum glutamine oxalo-transaminase (SCOT), lactate dehydrogenase (LDH) and creatinine phosphokinase (CPK). Five out of 11 children had a high serum enzyme level, ranging 25-68 U/dI (mean: 40.88 ÃÂ± 16.30) for GOT, 315 889 U/dI (mean: 482 ÃÂ± 232.53) for LDH, and 57-581 U/d1 (mean: 251.33 ÃÂ± 287.02) for CPK, instead of a normal level range of 1-19 U/c11, 80-240 U/dl and 0-50 U/dl respectively. It is concluded that the episode of SVT often occurs in children with infection, especially gastrointestinal intention, meningitis, encephalitis. bronchopneumonia and septicemia. Fever, undernutrition and anemic status are considered as precipitating factors. Preexitation syndromes, such as WPW and LGL syndromes, were infrequently found. Digitalis treatment has to be changed with other preparations which are often used such as calcium antagonist or ATP, especially for patients who do not respond to digitalis. Physicians who work in the surgery department, should be aware of an SVT episode, especially if the children have fever, undernutrition and anemia. Key Words: supraventricular tachycardia - anemia - undernutrition - WPW syndrome - LGL syndrome